Outcome of management of closed distal tibia fractures using staged surgical protocol - Kunwar, Suman Dhoj; Sitaula, Prakash; Thapa, Bishwamber; Thapa, Santosh; Rajthala, Ashish (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Complex fracture geometry and delicate soft tissues in the ankle region makes surgical treatment of distal tibial fractures challenging. In this study, we evaluated clinical and radiological outcomes following staged procedures for management of closed distal tibia fractures. METHODS: This is a retrospective study with two-staged procedure for management of distal tibia fracture of patients treated between September 2017 and October 2019. Initial management consisted of ankle-spanning external fixator application with or without fibular fixation. Definitive procedure was done after soft tissue healing. Either minimally invasive procedures or open reduction and plating were done on the basis of fracture geometry. Clinical outcome was evaluated based on fracture healing, soft-tissue problems and infection, pain and mobility. Olerud-Molander Ankle Scoring system (OMAS) was used for evaluation of functional outcome. RESULTS: Twenty-seven patients were included in the final evaluation and had at least one-year follow-up. Three patients (11.1 percent) had superficial infection with partial thickness skin necrosis and one (3.7 percent) had deep infection. There was no incidence of pin tract infection. Average fracture union time was 14 weeks (14.37 ± 1.735). Result of Olerud-Molander Ankle Scoring system (OMAS) score at one year was excellent in 22 patients (81.4 percent). CONCLUSION: This retrospective study showed a good clinical outcome in patients with closed distal tibia fractures managed with staged protocol with minimal complications, thus making an invaluable addition of cases to the existing literature. We believe that two-stage protocol can significantly reduce soft tissue complications inherent to this injury and provide better surgical outcome